2012
DOI: 10.1007/s00289-012-0759-1
|View full text |Cite
|
Sign up to set email alerts
|

Melt rheological properties of ETFE: an attempt to illuminate the fluorine-substitution effect

Abstract: Flow behaviors and rheological properties of ethylene tetrafluoroethylene alternating copolymer (ETFE) under high-shear conditions were first reported. Flow instabilities, shear and extensional viscosities, and die swell of ETFE were investigated. Rheological behaviors of perfluorinated ethylene propylene copolymers (FEP), partially fluorinated ETFE, and non-fluorinated polyethylenes (PE) were compared for understanding the role of fluorine incursion on materials properties. It is found that (1) ETFE does not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The fluoro-polymer ethylene(tetrafluoroethylene) (ETFE) is a copolymer of ethylene and tetrafluoroethylene and has been attracting more and more attention due to its excellent property [ 16 ]. ETFE material possesses novel toughness, flexibility, and relatively high stiffness ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluoro-polymer ethylene(tetrafluoroethylene) (ETFE) is a copolymer of ethylene and tetrafluoroethylene and has been attracting more and more attention due to its excellent property [ 16 ]. ETFE material possesses novel toughness, flexibility, and relatively high stiffness ability.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the copolymer is widely used in aerospace, nuclear utilization, and solar exploitation areas [ 17 ]. Correspondingly, ETFE films are intensively explored on the molecular parameters and microstructures [ 18 , 19 ], thermal and crystallization behaviors [ 20 , 21 ], and rheology property researches [ 16 , 22 ]. Recently, Chen et al [ 23 ] indicated that the flexible UV transparent ETFE mold could be fabricated by the hot embossing with the HSQ master template and further used to fabricate the OTFT device.…”
Section: Introductionmentioning
confidence: 99%